The Effect of Hypno-Teaching Toward Ability of Critical Thinking Students 2nd Level of Nursing Study Program, Stikes Santa Elisabeth Medan - LINDAWATI SIMORANGKIR; LINDAWATI SIMORANGKIR; LINDAWATI FARIDA TAMPUBOLON (International Journal of Nursing and Health Services (IJNHS), 2021)
Hypno-teaching is a creative, unique, and imaginative learning method. This study aims to determine the Effect of Hypno-Teaching Toward The Ability of Critical Thinking Students 2nd Level of Nursing Study Program, STIKes Santa Elisabeth Medan. The study design was classroom action research. This study's respondents were 74 students of Nurses level II, which obtain through the purposive sampling technique. These respondents divide into two groups: the intervention group using the Hypno-teaching method and the control group using the conventional learning method. Each group was 37 respondents. The results showed that the mean Ability of students' critical thinking in the intervention group before Hypno-teaching was 7.84 with a standard deviation of 3,648 after Hypno-teaching was 12.46 with a standard deviation of 3,671. The statistical test results showed that the value P = 0.000 means a positive difference in the average Ability of critical thinking of students between before and after Hypno-teaching, with an increase in the range of 4.62. The control group also found that the mean pretest scores of students were 10.78 with a standard deviation of 4.158, and the mean post-test scores were 13.27, with a standard deviation of 3.097. The results of statistical tests showed that the value of P = 0.004 means that there is a difference in the average Ability of critical thinking of students in a positive direction between before and after learning that using conventional methods, with an increased range was 2.49. This study showed that the Hypno-teaching method could improve students' critical thinking skills better than Sectional methods. These two methods influence students' critical thinking skills, but the average increase in Hypno-teaching reached 4.62, while in the conventional method only increases to 2.49